Efficacy of Herbicide Active Ingredients Against Aquatic Weeds - Kenneth Langeland; Michael Netherland; William Haller; Tyler Koschnick (EDIS, 2006)
SS-AGR-44, a 4-page fact sheet by K. Langeland, M. Netherland, W. Haller, and T. Koschnick, provides a table for quick reference to the effectiveness of herbicide active ingredients for controlling common aquatic weeds, and outlines the regulatory conditions and resources for further assistance. Published by the UF Department of Agronomy, September 2006.